Correlation between Nutritional Status and Fasting Blood Glucose Levels in the Elderly: An Investigative Study - Retno Dewi Noviyanti; Dewi Pertiwi Dyah Kusudaryati; An-Nisa Visi Asmara; Dhinda Kusuma Hatifah (Genius Journal, 2023)
Introduction: Elderly is an advanced stage of a life process which is characterized by a decrease in the body's ability. One of the diseases that often affects the elderly is diabetes mellitus. Blood glucose levels in patients with diabetes mellitus must be controlled to prevent complications. In addition to diet and drug use, nutritional status also plays a role in maintaining blood sugar. Objective: The purpose of this study was to determine the relationship between nutritional status and blood glucose levels in the elderly. Method:  The research method was cross sectional, with a sample of elderly people in the Gambirsari Surakarta health center area in August 2023, totaling 99 elderly people with an age range of 48 – 82 years. The variables studied were nutritional status and current blood glucose (GDS). Primary data collection method by measuring weight and height as well as examining the GDS. Data were analyzed with Spearman's rho. Result: The research results showed that the majority were female (73.7%), the age range was 48 – 82 years with an average age of 61.31 ± 6.77 years, an average nutritional status of 25.56 ± 4.85 kg/ m2 category, mostly fat, 54 people (54.5%), the average blood sugar level was 135.13 ± 63.26 mg/dL with the normal category 88.9%, abnormal 11.1%, correlation test results nutritional status with random blood sugar levels (p=0.012). Conclusion: The conclusion of the study is that there is a relationship between nutritional status and blood sugar levels during.